“Party Wing” Organizations as Potential Political Party Lawbreakers - hartanto Muhammad Afgan Ababil (Faculty of Law, Universitas Pekalongan, 2023)
Political parties and political party wings are organizations that play a role in democracy in Indonesia. Apart from that, there are still community organizations that appear to have no political affiliation but actually play a role in democratic contestation, then sporadically, almost every year before the election, similar community organizations emerge, which generally called volunteers. Political parties and their wing organizations have the same responsibility in building democracy, but we often find that party wing organizations can become an extension of political parties, committing various violations of campaigning rules or breaking the law in general; Here there is an intersection of whether political party wing organizations are subject to Law No. 2 of 2011 concerning political parties, or the law on social organizations. Researchers examine the problems of the existence of OSP in the Indonesian legal system, especially the phenomenon of legal violations. This research uses a normative juridical approach using legal norms that apply in Indonesia. At the end of the research, it was concluded that party wing organizations are more appropriately regulated in the political party law than in the law on social organizations, and violations are the responsibility of the parent political party.Keywords: law, politics, party, wing, underbouw